Trinidad Yoruba : From Mother-Tongue to Memory. - Warner-Lewis, Maureen (Caribbean archaeology and ethnohistory., 1996)
A deeply informed Afrocentric view of language and cultural retention under slavery. Maureen Warner-Lewis offers a comprehensive description of the West African language of Yoruba as it has been used on the island of Trinidad in the southern Caribbean. The study breaks new ground in addressing the experience of Africans in one locale of the Africa Diaspora and examines the nature of their social and linguistic heritage as it was successively retained, modified, and discarded in a European-dominated island community.